The linkage of water quality measurement the downstream of the Citarum cascade reservoir management - Lieza Corsita; Arwin Sabar; Barwin Setiani Muntalif; Indah Rachmatiah S. Salami (SINERGI, 2022)
Cascade Citarum Reservoirs, located in the western part of the island of Java in Indonesia country, cover the main building dams, hydropower, irrigation facilities and other supporting facilities. The study aimed to evaluate the characteristics of the existing condition of the downstream reservoir, including the relation of the water quality and quantity, by using a conceptual model of the Citarum Cascade Reservoir management. The study mostly used the secondary data acquired from Indonesia Power, the Management Bureau of Cirata Dam (BPWC), Perum Jasa Tirta II (PJT) Jatiluhur, the Management Bureau of the Citarum-Ciliwung River Basin (BPDAS Citarum-Ciliwung), and the Water Resource Management Agency of the West Java Province. This research aims to predict the discharge plans R5 and R20 using the Weibull method and the uncertainty of future discharge using the continuous model approach. Furthermore, the multivariate statistical test will analyse the linkage of water quality in reservoir management. To solve the problem of the allocation of the raw water discharge to fulfil the water requirement in the downstream area was developed proportionally in this study, in which the raw water discharge allocations were 46.92 m3/sec, 91.9 m3 /sec and  97.95 m3/sec for Saguling, Cirata, and Jatiluhur, respectively. The tests to determine the relationship between the discharge and water quality using the Discriminant test indicated that the discharge correlates strongly with the parameters such as NH3. BOD and COD.